Analisis Kepuasan dalam Meningkatkan Loyalitas melalui Kepercayaan: Studi pada Pasien Peserta BPJS di UPT Puskesmas Cimaragas Kabupaten Ciamis - Peni Cahyati (Neolectura, 2021)
This study aims to determine and analyze the effect of satisfaction on trust and its implications for loyalty (a study on BPJS participant patients at UPT Puskesmas Cimaragas, Ciamis Regency). The results of this study are expected to become input for the UPT Puskesmas Cimaragas, Ciamis Regency, which is useful for increasing satisfaction so that patient trust and patient loyalty can be achieved. The research method used is descriptive analysis and verification. The data collection used was interviews using a questionnaire accompanied by observation and literature techniques, the p-sampling technique was carried out by consecutive sampling using inclusion and exclusion criteria. Data collection in the field was carried out in 2019. Data analysis techniques used Path Analysis. The results showed that in general the satisfaction, trust, and loyalty of patients at the UPT Puskesmas Cimaragas, Ciamis Regency were in the poor category. There is an effect of satisfaction on trust and its implications for patient loyalty. The better the patient's satisfaction, the better the patient's trust in the Puskesmas, which in turn will have an impact on increasing patient loyalty at the UPT Puskesmas Cimaragas.